Answer:
b^-6
Step-by-step explanation:
(b^-2) / (b^4) = b^(-2 - 4)
Answer:
The answer is C
Step-by-step explanation:
Multiply all of the values by 2 and then you end up with the bigger triangle.
Answer:x^6-16^2/ -64
Step-by-step explanation:
Answer:
<u>aₙ = aₙ₋₁ - 3</u>
Step-by-step explanation:
Given :
First term : <u>33</u>
Common difference = 30 - 33 = <u>-3</u>
<u />
============================================================
Then the formula will be :
<u>aₙ = aₙ₋₁ - 3</u>
I think that the answer is b but I am not sure